On the difficulty of investing sustainably in the future. And how it can be done. Plus postscript: Future investments in the in times of the Corona pandemic - Michael Thöne (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2020)
This talk was delivered on 14 February 2020. It is now published as a discussion paper on 20 March 2020. Five weeks ago - in quite a different time. In the middle of the corona pandemic and at the beginning of a severe economic crisis, publishing a paper on long-term effective investments in the future and the sustainability of financial policy suddenly looks out of date. At first glance. Five weeks ago - in quite a different time. Of course, it is never outdated to talk about the future. And of course, we have to deal acutely and above all with the burning issues of crisis man- agement. With the up-to-the-minute postscript "Future investmentsin the in times of the Corona-pandemic", I would like to shed light on the rela- tionship between the short- and long-term challenges. The scale of the acute tasksisimmense. But the damage from the current crisis will be even greater if it is played off against the structural tasks of the future. Here we can learn from the mistakes of the last economic crisis. Future investments in the in times of the corona pandemic The script of the talk from February is reproduced here essentially un- changed. In part, it contrasts with the following comments on fiscal policy in the Corona crisis. In other parts, it fits remarkably well. Ultimately, both parts look at the two sides of the same coin. Our tasks for the future will not disappear because we have to take acute care of the epidemic. The challenges have become considerably greater as a result, and our problem- solving capacities are even more required. The paper shows how we can take a holistic view of the responsibilities that have grown so dramatically - and then tackle them.
Additional information: This discussion paper is the English version of the FiFo DP 20-02: "Von der Schwierigkeit, tragfähig in die Zukunft zu investieren. Und wie es doch zu schaffen ist. Plus Nachbemerkung: Zukunftsinvestitionen in Zeiten der Corona-Pandemie." http://hdl.handle.net/10419/214907
Keywords: 330; Infrastrukturinvestition; Zukunft; Haushaltskonsolidierung; Wirtschaftskrise; Infektionskrankheit; Deutschland